2017
DOI: 10.1002/ange.201700324
|View full text |Cite
|
Sign up to set email alerts
|

B(C6F5)3‐Catalyzed Selective Chlorination of Hydrosilanes

Abstract: The chlorination of Si−H bonds often requires stoichiometric amounts of metal salts in conjunction with hazardous reagents, such as tin chlorides, Cl2, and CCl4. The catalytic chlorination of silanes often involves the use of expensive transition‐metal catalysts. By a new simple, selective, and highly efficient catalytic metal‐free method for the chlorination of Si−H bonds, mono‐, di‐, and trihydrosilanes were selectively chlorinated in the presence of a catalytic amount of B(C6F5)3 or Et2O⋅B(C6F5)3 and HCl wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…selective B(C6F5)3catalyzed hydrosilane acidolysis serves as a versatile route to organohydrochlorosilanes (Scheme 1c). 8 However, direct organochlorosilane hydrogenolysis as a source of hydrosilanes remains elusive due to the unfavorable thermochemistry (Me3SiCl + H2 → Me3SiH + HCl; DG 0 = +22.2 kcal mol -1 ). 8 Very recently, Shimada and co-workers pioneered 9 the hydrogenolysis of silyl triflates and halides R3-nSiXn+1 with iridium catalysts (Scheme 1d/e).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…selective B(C6F5)3catalyzed hydrosilane acidolysis serves as a versatile route to organohydrochlorosilanes (Scheme 1c). 8 However, direct organochlorosilane hydrogenolysis as a source of hydrosilanes remains elusive due to the unfavorable thermochemistry (Me3SiCl + H2 → Me3SiH + HCl; DG 0 = +22.2 kcal mol -1 ). 8 Very recently, Shimada and co-workers pioneered 9 the hydrogenolysis of silyl triflates and halides R3-nSiXn+1 with iridium catalysts (Scheme 1d/e).…”
Section: Introductionmentioning
confidence: 99%
“…8 However, direct organochlorosilane hydrogenolysis as a source of hydrosilanes remains elusive due to the unfavorable thermochemistry (Me3SiCl + H2 → Me3SiH + HCl; DG 0 = +22.2 kcal mol -1 ). 8 Very recently, Shimada and co-workers pioneered 9 the hydrogenolysis of silyl triflates and halides R3-nSiXn+1 with iridium catalysts (Scheme 1d/e). 10 With relatively high catalyst loadings (5-10 mol-%) and long reaction times (2-7 days), moderate yields around 50-60 % in Me2SiH2 and Me2SiHCl could be obtained upon hydrogenolysis of Me2SiOTf2 or in situ prepared Me2SiI2 and Me2SiICl, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Notably,D obrovetsky et al recently reported aB(C 6 F 5 ) 3 -catalyzed selective chlorination of hydro- silanes using HCl as the chlorinating agent. [12] However, alarge excess gaseous HCl was employed in this method in an uncontrollable way.C onsequently,t he development of an operationally simpler and green catalytic procedure for chlorinating of hydrosilanes is appealing and highly desirable. Herein, we describe agreen and selective method to generate chlorosilanes through neutral eosin Y-catalyzed HATw ith hydrosilanes under visible-light irradiation using dichloromethane (DCM) as both the chlorinating agent and solvent (Scheme 1c).…”
mentioning
confidence: 99%